The Intellectual Controversy Between Abraham Geiger and Al-Ghazali in Interpreting Islam - Marsella, Marsella; Turjiman, Lalu (Abrahamic Religions: Jurnal Studi Agama-Agama, 2025)
The differences in thought between Abraham Geiger and Al-Ghazali in understanding Islam reflect two contrasting approaches to the Qur’an and the influence of tradition in religious education. This study aims to analyze how their intellectual perspectives have shaped theological development within their respective traditions and their impact on the broader study of religion. The research employs a qualitative method, focusing on an in-depth analysis of Geiger’s and Al-Ghazali’s works, alongside a comprehensive literature review to contextualize the historical and philosophical dimensions of their arguments. The findings indicate that Geiger, through his historical-critical approach, presents a more flexible interpretation of sacred texts, whereas Al-Ghazali upholds the authority and wisdom of the Qur’an as the primary foundation of Islamic knowledge. This intellectual discourse highlights the tension between rationalism and traditionalism in Islamic studies while illustrating the dynamic interplay between radicalism and religiosity within the Muslim world. Furthermore, this controversy underscores internal debates across various religious traditions and offers valuable insights into how interfaith dialogue can enhance the understanding of Islam and spirituality in the modern era. Ultimately, this study aims to contribute to a broader academic discourse on the interaction between religious tradition and critical thought in a global context.